PERAN PERSEPSI KUALITAS PRODUK DALAM MEMEDIASI PENGARUH GAYA HIDUP TERHADAP NIAT BELI HANDPHONE SAMSUNG GALAXY DI KOTA DENPASAR - Indrayani, Linda; Nurcaya, I Nyoman (E-Jurnal Manajemen; Vol 3 No 4 (2014), 2014)
The purpose of this research is to find out how internal and external factors from a product can impact the customer’s intention to buy the product. This research was held in the capital city of Bali, Denpasar. This research explains about how quality perception as external factor mediates the impact of lifestyle to purchase intention of Samsung Galaxy. The sample in this research is 150 who don’t have product Samsung Galaxy in Denpasar. According to the result, lifestyle impacts  perceived product quality significantly and perceived product quality impacts purchase intention significantly. Keywords: lifestyle, perceived product quality, purchase intention
Keywords: lifestyle,preceived product quality , purchase intention